Finite element modeling and fatigue life prediction of helicopter composite tail structure under multipoint coordinated loading spectrum - Wan, Ao-Shuang; Xu, Yigeng; Xue, Li-Heng; Xu, Ming-Rui; Xiong, Junjiang (Elsevier, 2020)
This paper presents a numerical study on fatigue life prediction of helicopter composite tail structure under multipoint coordinated loading spectrum. The FE model of a full-scale helicopter composite tail structure was established and then validated with the experimental results of strain and displacement distributions. Good agreement has been achieved between simulation and experiments under two multipoint coordinated static loading conditions representing left yawing and two-point horizontal landing. A progressive damage analysis was performed on the tail structure model under multipoint coordinated spectrum loading. The predicted fatigue life of the helicopter tail structure is 64 repeated applications of the load spectrum. No element failure was predicted on the tail structure after 48 repeated applications of the load spectrum. The impact damage introduced on the left-side wall thereafter propagated after another 6 repeated applications of the load spectrum, which agrees well with experimental observations. The progressive damage analysis has been shown to be a practical engineering tool for life prediction of helicopter composite structures
Keywords: Progressive damage analysis; Spectrum loading; Helicopter composite structure; Fatigue life prediction; FE modeling